Chromatography hardware improvements for reactive molecule separations
Patent Information
- Application Number
- CN202180063316.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-24
- Filing Date
- 2021-09-24
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2041-09-24
AI Technical Summary
本技术的特征还在于将表面涂层施加到液相色谱系统的其他金属部件(例如,玻璃料、管材、连接器、样品贮存器和进样器、和/或柱)以解决液相色谱系统中的分析物降解问题
[0020] The aforementioned aspects and features of this technology offer numerous advantages. For example, the apparatus and methods of this disclosure reduce the detrimental results of using metal-based glass frits in liquid chromatography systems. Using this technology, active sites on the metal surfaces of stainless steel or other metals (e.g., titanium or titanium alloys) can be masked to prevent on-column metal-catalyzed analyte interactions, such as oxidation or nitrosation. In particular, the method of this technology allows the application of inorganic-organic hybrid surfaces to coat and thus mask the underlying metal glass frit or other hardware used within the liquid flow path to reduce on-column degradation, thereby increasing the intensity of analytical results.
Smart Images

Figure CN116391122B_ABST
Abstract
Description
[0001] Cross-references to related applications
[0002] This patent application claims priority and benefit to U.S. Provisional Patent Application No. 63 / 082,539, filed on September 24, 2020, entitled “Chromatographic Hardware Improvements for the Separation of Reactive Molecules,” the entire contents of which are incorporated herein by reference. Technical Field
[0003] This disclosure relates to apparatus and techniques for improving the separation of reactive molecules. More specifically, this technique relates to apparatus and techniques for reducing or eliminating on-column analyte degradation. Background Technology
[0004] Analytes that interact with metals often prove extremely challenging to separate. The desire for highly efficient chromatographic systems with minimal dispersion necessitates smaller flow path diameters and the ability to withstand increasingly higher pressures at increasingly faster flow rates. Therefore, the materials chosen for chromatographic flow paths are often inherently metallic. This is despite the fact that certain analytes (e.g., biomolecules, proteins, glycans, peptides, oligonucleotides, pesticides, bisphosphonates, anionic metabolites, and zwitterions such as amino acids and neurotransmitters) are known to have unfavorable interactions with metal surfaces (so-called chromatographic secondary interactions).
[0005] The proposed mechanism for metal-specific binding interactions requires an understanding of Lewis acid-base chemistry. Pure metals and metal alloys (along with their corresponding oxide layers) have terminal metal atoms that exhibit Lewis acid properties. More simply, these metal atoms show a tendency to accept donor electrons. This tendency is even more pronounced for any surface metal ions carrying a positive charge. Analytes with sufficient Lewis base properties (any substance that can provide non-bonding electrons) can potentially adsorb onto these sites, forming problematic non-covalent complexes. It is these substances that are defined as analytes that interact with metals.
[0006] For example, analytes with phosphate groups are excellent polydentate ligands capable of high-affinity metal chelation. This interaction leads to the binding of phosphorylated substances to flow path metals, thereby reducing the amount of such substances detected. This is a particularly troublesome effect because phosphorylated substances are often the most important analytes in the assay.
[0007] Other properties of the analyte can also cause problems. For example, carboxylic acid ester groups also have the ability to chelate metals, although with a lower affinity than phosphate ester groups. However, carboxylic acid ester functional groups are ubiquitous in, for example, biomolecules, thus providing opportunities for accumulated polydentate-based adsorption losses. These complexities exist not only in peptides and proteins but also in glycans. For example, N-glycans can sometimes contain one or more phosphate ester groups and one or more carboxylic acid esters containing sialic acid residues. In addition, smaller biomolecules (such as nucleotides and sugars, such as sugar phosphate esters) can exhibit similar behavior to the aforementioned N-glycan molecules. Furthermore, chromatographic secondary interactions can be particularly problematic for biomolecules, especially larger structures, because they have the ability to form microenvironments (by their size and structural sequence) that can interact adversely with the surfaces of the separation components and flow paths. In this case, biomolecules or analytes with larger structures can present structural regions with chemical properties that amplify secondary interactions with materials within the flow path. This, combined with the cumulative metal chelation effect, can weaken the overall effective separation of biomolecules, pesticides, bisphosphonates, anionic metabolites, and zwitterions such as amino acids and neurotransmitters.
[0008] Besides adsorption on metal surfaces, reactive metals can cause other problems. Specifically, unwanted metals can catalyze reactions throughout the liquid chromatography system, leading to on-column degradation. For example, on-column degradation can result from the adsorption of dissolved metal ions (single metals, metal oxides, or clusters of molecules) onto the surface of the glass frit or the stationary phase. Unwanted reactive metals can also appear from the reaction of small insoluble metal or metal oxide particles with metal surfaces (such as glass frits, tubing, etc.) or from metal precipitates collected at the column head.
[0009] Separation systems typically incorporate stainless steel, not only as conduits or columns but also as hardware within the flow path, such as glass frit. The use of stainless steel hardware can lead to on-column analyte degradation due to interactions with exposed metal surfaces, such as conduits, columns, and glass frit. Because glass frit is completely contained within the column, it can facilitate on-column reactions and result in undesirable analyte adsorption.
[0010] To address these issues, metals with fewer problems than stainless steel (such as titanium and titanium alloys) have been used to form glass frits. However, these less problematic materials can still lead to undesirable analyte adsorption and contribute to on-column reactions. Adsorption losses in laboratory glassware (such as glass frits) reduce the intensity of analytical results.
[0011] Therefore, continuous efforts are needed to reduce the interaction between the wetted surface and the fluid sample in order to provide improved results. Summary of the Invention
[0012] Typically, this technique involves applying a surface coating to a metallic glass frit to address on-column analyte degradation. This technique is further characterized by applying a surface coating to other metallic components of a liquid chromatography system (e.g., glass frit, tubing, connectors, sample reservoirs and injectors, and / or columns) to address analyte degradation issues within the liquid chromatography system. In some embodiments, the surface coating is an inorganic-organic hybrid coating that can be vapor-deposited to cover the outer surface of a metallic glass frit (such as stainless steel glass frit and non-stainless steel glass frit (e.g., titanium)). Using this technique, active sites on the metallic surface of the glass frit can be masked to prevent on-column metal-catalyzed analyte reactions, such as oxidation, amination, nitrosation, or nitration. Applying a surface coating (e.g., an inorganic-organic hybrid surface) to a metallic glass frit reduces on-column degradation compared to the uncoated corresponding metallic glass frit. Typically, the application of a surface coating eliminates or reduces the number of metallic surface sites available for reaction with the analyte.
[0013] In one aspect, the technology relates to a chromatographic column. The chromatographic column includes a glass frit comprising a metallic substrate and an external coating surrounding at least a portion of the surface of the substrate, wherein the external coating comprises an inorganic-organic hybrid.
[0014] The foregoing aspects may include one or more of the following features. In one embodiment, the metal substrate comprises substantially pure titanium. In some embodiments, the outer coating may comprise C2 and / or C2C10. In some embodiments, the glass frit may also include an intermediate coating disposed between at least a portion of the outer coating and the surface of the metal substrate. The intermediate coating may be a pure metal, a metal oxide, a metal nitride, or a metal carbide. In some embodiments, at least a portion of the exposed metal wall contained within the chromatographic column comprises a fluid-containing coating comprising an inorganic-organic hybrid, such as, for example, C2 and / or C2C10.
[0015] In one aspect, the present technology relates to a method for reducing metal-catalyzed reactions (e.g., degradation) of sample components (e.g., amines) during liquid chromatography. The method includes separating a sample in a chromatographic column comprising a masking metallic glass frit, wherein the masking metallic glass frit comprises a metallic glass frit having an inorganic-organic hybrid coating on its outer surface that is non-reactive to the sample; and detecting the separated sample components using a detector. In some embodiments, an inert LC chromatography system is used to separate the sample, the inert LC chromatography system comprising a column and other hardware having all or most of its metal-wetting surfaces coated with an inert coating, such as, for example, the same as the inorganic-organic hybrid coating on the metallic glass frit. In some embodiments, the inert LC chromatography system also includes a bio-inert pump to deliver solvent to the chromatographic column.
[0016] The foregoing aspects may include one or more of the following features. In one embodiment, the masking metallic glass frit comprises pure or substantially pure (e.g., 97% purity or higher) titanium glass frit, and then an inorganic-organic hybrid coating is applied to the exterior of the titanium glass frit. In one embodiment, the masking metallic glass frit comprises a titanium alloy glass frit, and then an inorganic-organic hybrid coating is applied to the exterior of the titanium alloy glass frit. The masking metallic glass frit (i.e., including the inorganic-organic coating) reduces the number of sites within the system that react with the sample or solvent. In some embodiments, the masking metallic glass frit comprises a stainless steel glass frit, and then an inorganic-organic hybrid coating is applied to the exterior of the stainless steel glass frit. In some embodiments, the glass frit includes an intermediate coating applied prior to the external inorganic-organic hybrid coating, the intermediate coating comprising a layer of metal (e.g., titanium, titanium alloy, platinum, etc.), metal oxide, metal nitride, or metal carbide. In some embodiments, the intermediate coating provides pore-sealing and chemical stability properties to the underlying metallic substrate. For example, some metal oxides used to seal the orifice and provide chemical stability include, but are not limited to, Al₂O₃, TiO₂, Ta₂O₅, and ZrO₂. In some embodiments, the intermediate coating is applied simultaneously with the inorganic-organic hybrid coating (e.g., at the same time, or in the same reaction chamber). In some embodiments, the metal-containing coating comprises titanium (e.g., pure titanium, titanium alloys, titanium oxide). In some embodiments, the inorganic-organic hybrid coating is an organic silica coating. In some embodiments, the inorganic-organic hybrid coating is an alkylsilyl coating. In some embodiments, in addition to including a masking metal glass frit, the exposed metal walls within the column (or metal surfaces within the LC system) are also coated with an inorganic-organic hybrid coating. The inorganic-organic hybrid coating prevents or reduces catalytic reactions with the sample and / or with the solvents used in the LC system.
[0017] In one aspect, the present technology relates to a method for improving chromatographic performance in the separation of samples including amines. The method includes separating a sample in an inert liquid chromatography system comprising a column including titanium glass frit coated with an inorganic-organic hybrid coating; and detecting the separated components using a UV detector or an MS detector. In some embodiments, the method further includes providing a bio-inert pump (as part of the inert liquid chromatography system) to deliver solvent to the chromatographic column. In some embodiments of the method, the inert liquid chromatography system is characterized by including an internal column surface having an inorganic-organic hybrid coating.
[0018] The foregoing aspects may include one or more of the following features. In one embodiment, the titanium glass frit is coated with one or more layers of C2. In some embodiments, the titanium glass frit is coated with a C2 base layer and a C2C10 top layer. In one embodiment, the titanium glass frit is coated with a glycol-encapsulated inorganic-organic hybrid coating. In other embodiments, the titanium glass frit is coated with a phenyl-encapsulated inorganic-organic hybrid coating.
[0019] In another aspect, this technology relates to an inert glass charge for a liquid chromatography column. The inert glass charge comprises a stainless steel substrate comprising a multilayer coating. The multilayer coating comprises a titanium layer adjacent to the stainless steel substrate and an outer layer. The outer layer comprises an inorganic-organic hybrid coating. In another aspect, this technology relates to an inert glass charge comprising a substantially pure titanium substrate (e.g., less than 5% impurities, less than 3% impurities, less than 1% impurities), wherein a vapor-deposited C2 coating and / or C2C10 coating covers all outer surfaces to prevent analyte-metal interactions in the liquid chromatography column. Still in another aspect, this technology relates to an inert glass charge for a liquid chromatography column. The inert glass charge comprises a substantially pure titanium substrate, wherein a vapor-deposited C2C10 coating covers all outer surfaces to prevent analyte-metal interactions in the liquid chromatography column.
[0020] The aforementioned aspects and features of this technology offer numerous advantages. For example, the apparatus and methods of this disclosure reduce the detrimental results of using metal-based glass frits in liquid chromatography systems. Using this technology, active sites on the metal surfaces of stainless steel or other metals (e.g., titanium or titanium alloys) can be masked to prevent on-column metal-catalyzed analyte interactions, such as oxidation or nitrosation. In particular, the method of this technology allows the application of inorganic-organic hybrid surfaces to coat and thus mask the underlying metal glass frit or other hardware used within the liquid flow path to reduce on-column degradation, thereby increasing the intensity of analytical results. Attached Figure Description
[0021] The present technology will be more fully understood through the following detailed description taken in conjunction with the accompanying drawings, in which:
[0022] Figure 1A This is a schematic diagram of the chemical formula of Litronesib (an amine).
[0023] Figure 1B This is a schematic diagram of the chemical formula of the nitrosyl impurity (Z isomer) of Litronesib.
[0024] Figure 1C This is a schematic diagram of the chemical formula of the nitrosyl impurity (E isomer) of Litronesib.
[0025] Figure 1DThis is a chromatogram of litronesib separation, which contains nitrosyl impurities due to the nitrosation of litronesib during separation.
[0026] Figure 1E This is a UV chromatogram of litronesib separation, which contains nitrosyl impurities due to the nitrosation of litronesib during separation.
[0027] Figure 2A This is a schematic diagram of the chemical formula of the amine Clozapine.
[0028] Figure 2B This is a schematic diagram of the chemical formula of the n-oxide of clozapine.
[0029] Figure 3 This is a schematic diagram of a chromatographic flow system including a chromatographic column and various other components, according to an exemplary embodiment of the present technology. Fluid is carried through the chromatographic flow system, wherein the fluid flow path extends from the fluid manager to a detector such as an MS detector.
[0030] Figure 4 This is a flowchart illustrating a method for reducing the degradation of sample components during liquid chromatography according to an embodiment of the present technology.
[0031] Figure 5 This is a cross-sectional schematic diagram of an embodiment of the glass material according to the present technology.
[0032] Figure 6 This is a cross-sectional schematic diagram of an embodiment of the glass material according to the present technology.
[0033] Figure 7A This is a UV chromatogram of clozapine using a stainless steel column after a single injection.
[0034] Figure 7B This is a UV chromatogram of clozapine obtained using a stainless steel column after two injections.
[0035] Figure 7C This is a UV chromatogram of clozapine obtained using a stainless steel column after thirteen injections.
[0036] Figure 8A This is a TIC chromatogram of clozapine using a stainless steel column after two injections.
[0037] Figure 8B This is the TIC chromatogram of clozapine using a stainless steel column after 34 injections.
[0038] Figure 9A This shows the mass spectra of clozapine identification.
[0039] Figure 9BThis shows the mass spectrum for the identification of clozapine's n-oxides.
[0040] Figure 10A The image shows a UV chromatogram of clozapine obtained after a single injection using a coated (i.e., C2-coated) stainless steel column with coated (i.e., C2-coated) Ti glass frit.
[0041] Figure 10B The image shows a UV chromatogram of clozapine obtained after two injections using a coated (i.e., C2-coated) stainless steel column with coated (i.e., C2-coated) Ti glass frit.
[0042] Figure 10C The image shows a UV chromatogram of clozapine obtained after thirteen injections using a coated (i.e., C2-coated) stainless steel column with coated (i.e., C2-coated) Ti glass frit.
[0043] Figure 11A The TIC chromatogram of clozapine is obtained after two injections using a coated (i.e., C2-coated) stainless steel column with coated (i.e., C2-coated) Ti glass frit.
[0044] Figure 11B The TIC chromatogram of clozapine was obtained after 34 injections using a coated (i.e., C2-coated) stainless steel column with coated (i.e., C2-coated) Ti glass frit.
[0045] Figure 12A This is a TIC chromatogram of clozapine separation using a C2-coated stainless steel column with uncoated stainless steel glass frit. The TIC chromatogram focuses on the n-oxide peak after the second injection.
[0046] Figure 12B This is a TIC chromatogram of clozapine separation using a C2-coated stainless steel column with C2-coated stainless steel glass frit. The TIC chromatogram focuses on the n-oxide peak after the second injection.
[0047] Figure 12C This is a TIC chromatogram of clozapine separation using a C2-coated stainless steel column with uncoated titanium glass frit. The TIC chromatogram focuses on the n-oxide peak after the second injection.
[0048] Figure 12D This is a TIC chromatogram of clozapine separation using a C2-coated stainless steel column with C2-coated titanium glass frit. The TIC chromatogram focuses on the n-oxide peak after the second injection.
[0049] Figure 12EThis is a TIC chromatogram of clozapine separation using a C2-coated stainless steel column with uncoated stainless steel glass frit. The TIC chromatogram focuses on the n-oxide peak after the second injection.
[0050] Figure 13A This is a TIC chromatogram of clozapine separation using a C2-coated stainless steel column with uncoated stainless steel glass frit. The TIC chromatogram focuses on the n-oxide peak after the fifth injection.
[0051] Figure 13B This is a TIC chromatogram of clozapine separation using a C2-coated stainless steel column with C2-coated stainless steel glass frit. The TIC chromatogram focuses on the n-oxide peak after the fifth injection.
[0052] Figure 13C This is a TIC chromatogram of clozapine separation using a C2-coated stainless steel column with uncoated titanium glass frit. The TIC chromatogram focuses on the n-oxide peak after the fifth injection.
[0053] Figure 13D This is a TIC chromatogram of clozapine separation using a C2-coated stainless steel column with C2-coated titanium glass frit. The TIC chromatogram focuses on the n-oxide peak after the fifth injection.
[0054] Figure 13E This is a TIC chromatogram of clozapine separation using an uncoated stainless steel column with uncoated stainless steel glass frit. The TIC chromatogram focuses on the n-oxide peak after the fifth injection.
[0055] Figure 14A This is a TIC chromatogram of clozapine separation using a stainless steel column with uncoated stainless steel glass frit. The TIC chromatogram focuses on the z-isomer and e-isomer of the nitrosamine impurity peak of clozapine after the second injection.
[0056] Figure 14B This is a TIC chromatogram of clozapine separation using a stainless steel column with uncoated stainless steel glass frit. The TIC chromatogram focuses on the z-isomer and e-isomer of the nitrosamine impurity peak of clozapine after the thirty-fourth injection.
[0057] Figure 15A This is a TIC chromatogram of clozapine separation using a C2-coated stainless steel column with C2-coated Ti glass frit. The TIC chromatogram focuses on the positions of the z-isomer and e-isomer of the clozapine nitrosamine impurity peak after the second injection.
[0058] Figure 15BThis is a TIC chromatogram of clozapine separation using a C2-coated stainless steel column with C2-coated Ti glass frit. The TIC chromatogram focuses on the positions of the z-isomer and e-isomer of the clozapine nitrosamine impurity peak after the thirty-fourth injection.
[0059] Figure 16A This is a mass spectrometry showing the identification of baicalein and baicalein oxide during the first injection of a sample onto an uncoated stainless steel column.
[0060] Figure 16B This is a mass spectrometry showing the identification of propyl gallate and propyl gallate oxide during the first injection of a sample onto an uncoated stainless steel column.
[0061] Figure 16C This is a mass spectrometry showing the identification of baicalein and baicalein oxide during the first injection of a sample onto a C2-coated stainless steel column.
[0062] Figure 16D This is a mass spectrometry showing the identification of propyl gallate and propyl gallate oxide during the first injection of a sample onto a C2-coated stainless steel column. Detailed Implementation
[0063] Generally, this disclosure relates to apparatus and methods for creating inert liquid chromatography (LC) systems. Specifically, this disclosure relates to applying an inorganic-organic hybrid coating to an underlying metal substrate to form a mask, thereby reducing or preventing analyte-metal interactions in the LC system. In embodiments, the inorganic-organic hybrid coating is vapor-deposited to generate a uniform coating. In particular, this technology relates to apparatus or systems including an inorganic-organic hybrid coating for masking metallic glass frits (e.g., titanium glass frits, metallic glass frits with titanium layers) used in inert liquid chromatography systems. In some cases, this technology relates to methods for providing coated glass frits to a system (and particularly coated inert LC systems) to reduce on-column degradation and thereby increase the intensity of analytical results.
[0064] Various conditions are used in liquid chromatography (LC) to optimize the performance of analyte separation. In chromatographic methods (such as reversed-phase chromatography), an aqueous mobile phase and organic solvents are typically used to elute analytes. Acetonitrile and methanol are commonly used solvents for elution, but they have been shown to corrode stainless steel and other metals over time. This corrosion can cause the metal surfaces of the LC system or column (especially with regard to glass frit) to become catalytically active. This can lead to analyte-metal interactions, resulting in the degradation of sample components.
[0065] Two examples of metal-catalyzed analyte reactions include nitrosation and oxidation. That is, the active surface of a metal exposed to an organic solvent provides active sites for reaction with certain analytes, such as amines. For example, litrosiba (a kinin inhibitor often investigated as a potential therapy in cancer treatment) can be converted into an impurity in a metal-catalyzed reaction via nitrosation, thereby degrading analytical separation results. (See reference...) Figure 1A The chemical formula of Litronesib is shown. In catalytically active environments (such as those with exposed metals, acetonitrile, and / or methanol), the polar covalent NH at the base of this structure can react in nitrosation reactions to form the Z isomer ( Figure 1B ) or E isomer ( Figure 1C As a result of the nitrosation reaction, some original sample materials are transformed into different forms, which will change the analytical results of the study. For example, Figure 1D Chromatograms for the separation of known amounts of Libronesib are provided (from Myers et al., Journal of Chromatography A, Vol. 1319, December 6, 2013, pp. 57-64). Impurity peaks are present in the spectrum due to the partial nitrosation of the analyte into impurity forms (Z or E isomers), thus reducing the quality of the results. See also... Figure 1E The results provided by the UV detector showed that Litronesib was degraded by nitrosation.
[0066] Oxidative catalytic reactions can also occur during chromatographic separation, involving metals within the flow path. For example, clozapine (an amine and antipsychotic drug) is known to react in separation environments with exposed metals and organic solvents. During separation, at least a portion of clozapine within the sample can be converted to n-oxides due to active metal sites and organic solvents. Figures 2A to 2B The chemical formulas of clozapine and its n-oxides are shown.
[0067] Besides amines, other analytes are also prone to on-column degradation. For example, aniline is known to degrade during dimerization when exposed to metal LC components in the presence of ammonium hydroxide and acetonitrile. Furthermore, in metal LC systems using formic acid and acetonitrile as the mobile phase, various additives (e.g., flavorings, food additives) (such as baicalin, scutellarin, and propyl gallate) are known to undergo polyphenol oxidative degradation.
[0068] To address these degradation issues, several alternative surfaces have been proposed over the years, including the use of titanium or titanium alloys instead of stainless steel. Titanium and its alloys are known to be less reactive in organic solvents than stainless steel. However, titanium has been shown to retain chromatographic reactivity and facilitate analyte adsorption. Furthermore, it has been found that titanium surfaces can leach ions when used with methanol (a common LC solvent). Thus, metal-catalyzed reactions from the column, its components (e.g., glass frit), or the LC system can still occur.
[0069] In this technique, applying an inorganic-organic hybrid vapor deposition coating (e.g., alkylsilyl coatings, glycol coatings, phenyl coatings, other ligand-based coatings) to stainless steel or other metallic materials prevents degradation caused by column or LC systems. The inorganic-organic hybrid coating masks the metal surfaces of columns and LC systems, protecting them from corrosion caused by mobile phases such as acetonitrile and methanol, or even the analyte itself. If active sites on the metal surface are masked, the inorganic-organic hybrid coating prevents corrosion of the underlying metal and thus prevents analyte degradation. By utilizing vapor deposition, a uniform coating can be achieved on the glass frit to mask active sites while still allowing them to pass through. Degradation reductions have been achieved on many different metallic substrates, not only titanium and its alloys, but also stainless steel.
[0070] In some embodiments, the technique includes multiple layers or coatings to mask active sites. For example, in some embodiments, a multilayer inorganic-organic hybrid coating is applied on top of a metallic glass frit. The multilayer coating may be a single material (e.g., C2 or C2C10), wherein a base layer is first applied and then accumulated in a second layer. Alternatively, the multilayer coating may contain two different materials. For example, a C2 base layer is directly vapor-deposited onto a titanium glass frit, followed by a growth layer or secondary layer containing C2C10. In some embodiments, the glass frit may be pretreated prior to the application of the inorganic-organic hybrid coating. For example, a stainless steel glass frit may be metallized with different metallic materials to reduce active sites before the application of the inorganic-organic hybrid coating. For example, a single metallic material (such as Ti) may be applied as the base coating material. In other embodiments, an alloy may be applied to the glass frit prior to the inorganic-organic hybrid coating. In some embodiments, a metal oxide, metal nitride, or, in some cases, a metal carbide base coating is applied to the stainless steel glass frit. In one embodiment, a titanium coating is applied as a substrate layer (e.g., by spraying or vapor deposition) onto a metallic glass frit; subsequently, an inorganic-organic hybrid coating (e.g., C2) is vapor-deposited onto the Ti-metallized stainless steel glass frit. In another embodiment, a bilayer consisting of alumina and titanium dioxide or alumina and tantalum oxide is applied via vapor deposition to a stainless steel glass frit (or other component) substrate, followed by the vapor deposition of an inorganic-organic hybrid coating onto the exterior.
[0071] In some aspects, this technology relates to the use of masking glass frit within an inert LC system. In embodiments, this technology includes methods and systems that involve using a masking metallic glass frit (e.g., a metallic glass frit coated with an inorganic-organic hybrid) within an LC system adapted to reduce secondary interactions. For example, this technology includes using a C2-coated titanium glass frit within an LC system comprising a coating along its wetting flow path. In some embodiments, the wetting flow path includes a column and connecting tubing. In some embodiments, the wetting flow path extends from a sample reservoir through a sample injector to the connecting tubing, the column, and to one or more detectors downstream of the tubing. An example of such a system includes the system described in U.S. Patent Publication US 2020-0215457 (July 9, 2020), which is incorporated herein by reference. In some embodiments, the LC system also includes a dedicated pump with a bio-inert surface. Examples of commercially available pumps with biocompatibility include, but are not limited to, bioQSM (part number 18601541), bioQSM PLUS (part number 18601581), bioQSM-XR PLUS (part number 18601584), and bioBSM (part number 18601561), all of which are available from Waters Technologies Corporation (Milford, MA).
[0072] This technique also relates to methods for reducing the degradation of sample components during liquid chromatography. Typically, this method aims to mask metals within the flow path to reduce potential metal-catalyzed reactions, such as nitrosation and oxidation of sample components. Figure 3This is a representative schematic diagram of a chromatographic flow system / apparatus 100 that can be used to separate analytes (such as amines) from a sample. The sample may contain other analytes known to be readily degraded. For example, in some embodiments, the sample may include aniline or additives such as baicalein, scutellarin, propyl gallate, quercetin-e-rhamnoside, or rutin. The chromatographic flow system 100 includes several components, including a fluid manager system 105 (e.g., controlling the flow of the mobile phase through the system), tubing 110 (which may also be replaced by or used in conjunction with micromachining fluid conduits), a fluid connector 115 (e.g., a fluid cap), glass frit 120, a column 125 (which houses the glass frit 120 at its inlet and / or outlet), a sample injector 135 (which includes a needle (not shown) for inserting or injecting a sample into the mobile phase), a vial, settler, or sample reservoir 130 for holding the sample prior to injection, a detector 150 (such as a mass spectrometer), and a pressure regulator 140 for controlling the flow pressure. The inner surfaces of the components of the chromatographic system / apparatus form fluid flow paths with wetting surfaces. The fluid flow paths may have a length-to-diameter ratio of at least 20, at least 25, at least 30, at least 35, or at least 40. A pump for delivering the fluid is part of the fluid manager 105 and is not shown separately.
[0073] In this technique, the glass frit 120 is located within the fluid flow path and has a wetting surface. That is, the glass frit 120 is exposed to the organic solvent and the sample passing through it. Generally, metallic glass frits are preferred for several reasons. For example, metallic glass frits can be formed and shaped as desired. Metallic glass frits have known permeability and particle retention capabilities. In addition, metallic glass frits maintain their shape and structure even after prolonged use. However, metallic glass frits can lead to analyte loss by providing active sites for metal-catalyzed reactions. To reduce or prevent those reactions, but to maintain the structural integrity provided by the metallic glass frit, the method according to this disclosure uses a masked or coated metallic glass frit to separate the sample to prevent analyte-metal interactions in the liquid chromatography column 125.
[0074] Figure 4A flowchart illustrating the method of this technique is provided. Method 400 for reducing the degradation of sample components during analysis (e.g., liquid chromatography separation) includes: step 405, which uses a column with a masked metallic glass frit to separate a sample; and step 410, which uses a detector to detect the separated sample components. The masked metallic glass frit in step 405 is a metallic glass frit coated on its outer surface with an inorganic-organic hybrid coating deposited by vapor deposition. The coating on the masked or coated metallic glass frit forms a barrier to prevent interaction between the underlying metal and the organic solvent / sample flowing through and around the glass frit. That is, the coating prevents analyte-metal interactions and thus reduces the degradation of sample components during liquid chromatography.
[0075] Some embodiments of the method also include separating the sample in an inert liquid chromatography system that includes not only a masking metallic glass frit but also a coated wetting surface, as well as components (e.g., a sample injector and tubing connecting the column to other components), and in some cases, a bio-inert pump for delivering fluids.
[0076] Figure 5 The masking glass frit 500 shown includes a metal substrate 505 that provides structure and integrity to the glass frit and at least one coating 510. The at least one coating 510 is typically vapor-deposited, such that the entire exterior of the masking glass frit 500 is protected by the coating—ensuring that there are no active metal sites that could be used for solvent / analyte interactions.
[0077] The inorganic-organic hybrid coating protects the underlying metallic material from interaction with organic solvents / metal reactive analytes. In one embodiment, the inorganic-organic hybrid coating is an alkylsilyl coating. The alkylsilyl coating is inert to at least one of the analytes in the sample. In some embodiments, the alkylsilyl coating is an organic silica coating. In some embodiments, the alkylsilyl coating is an inorganic-organic hybrid material that forms or coats a wetting surface (e.g., almost the entire wetting surface, more than 95% of the exposed surface, more than 97% of the exposed surface, more than 99% of the exposed surface).
[0078] The inorganic-organic coating may have a contact angle of at least about 15°. In some embodiments, the coating may have a contact angle of less than or equal to 30°. The contact angle may be less than or equal to about 115°. In some embodiments, the contact angle of the coating is between about 15° and about 90°, in some embodiments it is between about 15° and about 105°, and in some embodiments it is between about 15° and about 115°. For example, the contact angle of the coating may be about 0°, 5°, 10°, 15°, 20°, 25°, 30°, 35°, 40°, 45°, 50°, 55°, 60°, 65°, 70°, 75°, 80°, 85°, 90°, 95°, 100°, 105°, 110°, or 115°.
[0079] The thickness of the inorganic-organic hybrid coating (e.g., alkylsilyl coating) can be at least approximately For example, the thickness can be between approximately to approximately Between. The coating thickness can be approximately
[0080] or The thickness of a coating (e.g., a vapor-deposited alkylsilane coating) can be optically inspected by the naked eye. For example, higher opacity and tinting indicate a thicker coating. When a coated part is observed under full-spectrum light (such as sunlight), the color changes from yellow to purple, then to blue, then to a slightly greenish hue, and finally back to yellow as the coating thickens. For example, when the thickness of an alkylsilane coating is... When the coating is yellow, it reflects light with peak wavelengths between 560 nm and 590 nm. When the thickness of the alkylsilane coating is... When the coating is applied, it can exhibit a purple hue and reflect light with peak wavelengths between 400 nm and 450 nm. When the thickness of the alkylsilane coating is... At this time, the coating can exhibit a blue color and reflect light with peak wavelengths between 450 nm and 490 nm. See, for example, Faucheu et al., Relating Gloss Loss to Topographical Features of a PVDF Coating, published October 6, 2004; Bohlin and Erik, Surface and Porous Structure of Pigment Coatings, Interactions with flexographic ink and effects of print quality, Dissertation, Karlstad University Studies, 2013:49.
[0081] Inorganic-organic hybrid coatings can be products of vapor-deposited bis(trichlorosilyl)ethane, bis(trimethoxysilyl)ethane, bis(trichlorosilyl)octane, bis(trimethoxysilyl)octane, bis(trimethoxysilyl)hexane, and bis(trichlorosilyl)hexane.
[0082] In some respects, at least a portion of the wetted surface is coated with multiple layers of the same or different alkylsilanes, wherein the thickness of the alkylsilane coating is related to the number of layering steps performed (e.g., the number of alkylsilane coating layers deposited on the wetted surface of a glass frit, or, in the case of an inert LC system, the number of alkylsilane coating layers deposited along the wetted surface such as column walls, fittings, injectors, etc.).
[0083] The metallic glass frit may have multiple coatings, such as multiple alkylsilyl coatings. For example, a second alkylsilyl coating may be in direct contact with a first or base alkylsilyl coating. In one embodiment, the titanium metallic glass frit is coated with a base coating of C2 and a second coating of C2C10.
[0084] In one aspect, the inorganic-organic hybrid coating is n-decyltrichlorosilane, (3-glycidoxypropyl)trimethoxysilane (GPTMS), hydrolyzed (3-glycidoxypropyl)trimethoxysilane (GPTMS), 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, trimethylchlorosilane, trimethyldimethylaminosilane, methoxy-polyvinyloxy(3)silane, propyltrichlorosilane, propyltrimethoxysilane, (heptadecylfluoro-1,1,2, 2-Tetrahydrodecyl)tris(dimethylamino)silane, (heptadecano-1,1,2,2-tetrahydrodecyl)trichlorosilane, (heptadecano-1,1,2,2-tetrahydrodecyl)trimethoxysilane, vinyltrichlorosilane, vinyltrimethoxysilane, allyltrichlorosilane, 2-[methoxy(polyvinyloxy)3propyl]trichlorosilane, 2-[methoxy(polyvinyloxy)3propyl]trimethoxysilane or 2-[methoxy(polyvinyloxy)3propyl]tris(dimethylamino)silane.
[0085] Besides alkylsilyl coatings, other coating materials are also possible. For example, other inorganic-organic hybrid coatings containing glycols, phenyl groups, or other ligands can be used to protect metallic glass frits from unwanted interactions.
[0086] In addition to applying an inorganic-organic hybrid coating to a metallic glass frit, other processes can be used to reduce undesirable degradation of sample components. For example, if a stainless steel glass frit is required due to its structural integrity, a metallic titanium external coating can be applied to its outer surface before or simultaneously with the vapor deposition of the inorganic-organic hybrid coating. Other types of metallization or metallic coatings (before depositing an external inorganic-organic hybrid coating) of the stainless steel glass frit (or other metallic LC components) are also possible. The stainless steel glass frit may be pre-coated with iron, silicon, manganese, nickel, molybdenum, tin, cobalt, aluminum, copper, vanadium, chromium, or boron, rather than being metallized with titanium. In some embodiments, the metallic glass frit may be coated with gold, platinum, silver, tungsten, tantalum, or iridium. In some embodiments, the stainless steel glass frit may be pre-coated or treated with carbon (e.g., a diamond film), phosphorus, or sulfur before depositing the external inorganic-organic hybrid to prevent analyte interactions.
[0087] The masking glass material may include multiple coatings. For example, refer to Figure 6 The image shows a masking glass 600 comprising a metal-containing layer 607 (e.g., a layer containing a metal, alloy, metal oxide, metal nitride, or metal carbide) covering a metal substrate 605, followed by one or more vapor-deposited inorganic-organic hybrid coatings 610.
[0088] In some embodiments, the metal-containing layer 607 is a single layer composed of a single material (e.g., a Ti layer, a Ti₂O₃ layer, etc.). The metal-containing layer 607 may also be a bilayer composed of two different materials (e.g., an alumina layer followed by a titanium dioxide layer). The metal-containing layer 607 may comprise a pure or substantially pure elemental metal (e.g., Ti, Au, Pt). In other embodiments, the metal-containing layer is an alloy, such as Ti₆Al₄V. In some embodiments, the metal-containing layer is an oxide, nitride, or carbide. For example, the metal-containing layer may be alumina, silicon nitride, or titanium carbide. In embodiments, the metal-containing layer is vapor-deposited, and in the case of oxides, nitrides, or carbides, the vapor deposition utilizes oxygen, nitrogen, or carbon precursors in addition to the metal precursor. Table 1 provides a list of ligand types of interest for forming precursors used to form the metal-containing layer. Table 2 provides precursors for forming oxides, nitrides, and carbides. The precursors listed in Table 2 can be provided in an unactivated or plasma-activated state. In some implementations, the carbon precursors provided in Table 2 can be used in combination with metal oxides and nitrides to add organic bridges to these membranes.
[0089] Table 1: Types of ligands of interest for forming precursors for deposition
[0090] scandium Cyclopentadienyl, amide, imide, amidine yttrium Cyclopentadienyl, amide, imide, amidine titanium Halides, cyclopentadienyl, alkoxides, amides, imides, amidines zirconium Halides, cyclopentadienyl, alkoxides, amides, imides, amidines hafnium Halides, cyclopentadienyl, alkoxides, amides, imides, amidines vanadium Halides, alkoxides, amides, imides, amidines niobium Halides, alkoxides, amides, imides Tantalum Halides, alkoxides, amides, imides chromium Halides, alkoxides, amides, imides molybdenum Halides, amides, imides Tungsten Halides, amides, imides aluminum Halides, alkyl groups, alkoxides, amides, imides, amidines boron Halides, alkyl groups, alkoxides silicon Halides, alkyl groups, alkoxides, amides germanium Halides, alkyl groups, alkoxides, amidines
[0091] Table 2: Oxide, Nitride and Carbide Precursors
[0092] nitrogen precursor Nitrogen, ammonia, hydrazine carbon precursor Acetylene, formic acid, carbon (see ligands in Table 1), alcohol, acid, acid anhydride
[0093] The masked glass frit of this technology offers significant advantages compared to uncoated glass frit. In the Examples section below, evaluations of different glass frit materials using various LC systems demonstrate that this technology substantially reduces on-column catalytic reactions, such as oxidation and nitrosation, compared to uncoated hardware. Therefore, it provides more robust analysis and enhances results compared to conventional separation methods.
[0094] Example
[0095] Example 1: On-column oxidation using different column technologies
[0096] Clozapine was prepared in 0.1% (w / v) 20 / 80 / 0.08 (acetonitrile / water / acetic acid). These samples were analyzed using a Waters ACQUITYUPLC I-Class LC system and the separation methods outlined below. Figures 7A to 7C and Figures 8A to 8B The results of on-column oxidation separation from multiple injections on an uncoated stainless steel column (column A) are presented. Figures 10A to 10C and Figures 11A to 11BThe results of on-column oxidation separation from multiple injections on a C2-coated stainless steel column (column B) using C2-coated Ti glass frit are presented. Figure 9A The mass spectrum of clozapine at m / z = 327 was presented, while Figure 9B The mass spectrum of n-oxide clozapine at m / z = 343 is presented.
[0097] Table 3: Separation details of Example 1
[0098]
[0099] WO 2022 / 064447A1
[0100]
[0101] The choice of column technology affects metal-catalyzed reactions. In this embodiment, two types of columns were studied. Column A is an uncoated stainless steel column, while column B is a C2-coated stainless steel column.
[0102] Figures 7A to 7C The enhanced effect of metal-catalyzed reactions on the separation of clozapine on an uncoated column (column A) is shown. Figure 7A In the initial sample injection, a clean, flat peak for chlorine nitrogen was observed. However, after providing more sample to the system ( Figure 7B The two injections shown are as follows Figure 7C After 13 injections (as shown in the figure), clozapine oxide form appeared, thus degrading the results. Figure 8A and Figure 8B It was shown that the increase in oxide form continued to increase and greatly affected the results—comparison Figure 8A The oxide peaks after two injections and Figure 8B The oxide peak after 34 injections.
[0103] The degradation of the result can be minimized by selecting the column material. Figures 7A to 8B The spectra shown represent the results for an uncoated stainless steel column, exhibiting an increase in n-oxide peaks with increasing exposure to the sample and mobile phase. However, by selecting a different column technique, namely a stainless steel column coated with an inorganic-organic hybrid material (i.e., C2), the degradation of the results was minimized because the oxide peaks (when present) did not increase to the level shown. Figures 7A to 8B The same degree as shown. Figures 10A to 10C Spectra were provided on the C2-coated column after the first, second, and thirteenth (respectively) times. Figures 11A to 11B The changes in the n-oxide peaks between the second and thirty-fourth injections are shown.
[0104] Example 2: Column oxidation of different glass frit materials
[0105] Clozapine was prepared in 0.1% (w / v) 20 / 80 / 0.08 acetonitrile / water / acetic acid. These samples were analyzed using a coated inert system (ACQUITY UPLC PREMIER LC system, commercially available from Waters Corporation, Milford MA) and the separation methods outlined below. Figures 12A to 12D (After the second injection) and Figures 13A to 13D (After the fifth injection) separate on-column oxidation results were presented using different glass frit materials (e.g., uncoated metals such as stainless steel and titanium, and coated metals, including C2-coated stainless steel glass frit and C2-coated titanium glass frit) in multiple injections in the column (i.e., the second and fifth injections).
[0106] Table 4: Separation details of Example 2
[0107]
[0108] WO 2022 / 064447 A1
[0109]
[0110] As shown in the evaluation of different glass frit materials used with a hybrid organic-inorganic coating (C2 coating in this example), both stainless steel and titanium glass frits with C2 coating technology reduced on-column degradation of amines compared to their corresponding uncoated glass frits. Clozapine, a compound known to be oxidized on-column by an ammonium hydroxide and acetonitrile mobile phase, showed a 50% reduction in clozapine N-oxides when separated using C2-coated stainless steel glass frit compared to uncoated stainless steel glass frit. An 80% reduction was observed when using C2 on titanium glass frit compared to uncoated titanium glass frit.
[0111] Table 5: Percentage of chlordiazepoxide in total peak area
[0112]
[0113] SS = Stainless steel; Ti = Titanium; C2SS = C2 coating on stainless steel; C2Ti = C2 coating on titanium. See also Figures 12A to 12E and Figures 13A to 13E .
[0114] Interestingly, when comparing the performance of the studied glass frits, C2-coated titanium glass frit produced the least amount of oxidizing agents, followed by columns filled with titanium glass frit. While C2-coated stainless steel glass frit showed advantages over standard stainless steel glass frit, its effectiveness in preventing column oxidation was still 77% lower than that using titanium glass frit. There is reason to believe that C2 coating may not be effectively applied to stainless steel glass frit, and improved processes or the addition of a metal layer may prove more effective. However, C2 coating produces significantly lower oxidizing agents, and in the case of C2-coated titanium, it may even potentially prevent the formation of oxidizing agents, such as… Figure 11B This is illustrated by 34 injections onto a C2-coated stainless steel column containing a C2-coated Ti glass flot. For example, compare... Figure 11A and Figure 11B It shows very little oxide peak growth, or even no oxide peak growth at all.
[0115] Results using masked or coated glass frits also showed a reduction in nitrosation during the separation of clozapine using ammonium hydroxide and acetonitrile mobile phases. Although nitrosation of clozapine was less pronounced than that of its oxidative form, a reduction in nitrosation was also recorded. Figure 14A and Figure 14B Spectra at known clozapine nitrosamine impurity peaks (peaks of the z-isomer and e-isomer) are provided after the second and thirty-fourth injections of clozapine in an uncoated column using uncoated stainless steel glass flotation. Additional nitrosation occurs as more clozapine is injected into the system. However, nitrosation is inhibited in C2-coated stainless steel columns containing C2-coated titanium glass flotation. Figure 14A and Figure 14B The lack of growth of the mid-nitrosation peaks (e.g., the peaks at retention times 8.52 and 8.66) is related to... Figure 15A and Figure 15B The lack of mid-peaks is compared.
[0116] Therefore, in other embodiments of the invention, the hybrid organic-inorganic coating is not limited to C2 coatings, but can be applied to any coating or ligand that can mask metal-analyte interactions. Thus, different modes of chromatography and a wide variety of analytes (i.e., not just amines) can benefit from this protection. For example, this technique can be used for the separation or study of any metal-reactive analyte, such as aniline. It can also prevent or reduce degradation or alternative byproducts of metal-catalyzed reactions. It is foreseeable that this technique can be applied to the entire LC system or MS instrument, or even to different surfaces, such as sample vials or mobile phase containers, to prevent surface-catalyzed reactions that may occur within these instruments or containers.
[0117] Example 3: On-column oxidation using different column technologies
[0118] Scutellarin, scutellarin oxide, propyl gallate, and propyl gallate oxide were prepared in methanol / water (1:1, v / v) to generate single samples. The samples (i.e., the analytes in the samples) were analyzed using a Waters ACQUITY UPLC H-Class Bio Binary system and the separation conditions outlined below using stainless steel, an uncoated column with uncoated glass frit (Column A), and a coated stainless steel column with coated glass frit (Column B). The mobile phase consisted of acetonitrile and formic acid, which are known to cause polyphenolic oxidation of these analytes in the presence of metals. Figures 16A to 16B The results of on-column oxidation separation after the first injection on an uncoated stainless steel column (column A) are presented; and Figures 16C to 16D Results were presented on a C2-coated stainless steel column (column B). Mass spectra were presented, with the compounds and their oxidized forms labeled in the mass spectra. These spectra show that, compared to the coated column B (which consists of a titanium glass frit with a coating covering its wetting surface), the oxide peaks (i.e., scutellarin oxide and propyl gallate oxide) were significantly larger (i.e., containing a greater amount of oxide forms) in the uncoated column A.
[0119] Table 6: Separation details of Example 3
[0120]
[0121] WO 2022 / 064447 A1
[0122]
Claims
1. A chromatographic column, comprising: Glass material, the glass material comprising Metal substrate; An external coating surrounding at least a portion of the surface of the metal substrate, the external coating comprising an inorganic-organic hybrid; and An intermediate coating deposited by vapor deposition, disposed between the outer coating and the surface of the metal substrate. The intermediate coating is a metal-containing layer, wherein the metal-containing layer comprises titanium, metal oxide, metal nitride or metal carbide.
2. The chromatographic column of claim 1, wherein the metal substrate comprises substantially pure titanium.
3. The chromatographic column according to claim 2, wherein the outer coating comprises C2 and / or C2C10.
4. The chromatographic column of claim 1, wherein at least a portion of the exposed metal wall contained within the chromatographic column comprises a fluid contact coating, the fluid contact coating comprising an inorganic-organic hybrid.
5. The chromatographic column according to claim 1, wherein the inorganic-organic hybrid comprises C2 and / or C2C10.
6. The chromatographic column of claim 4, wherein the metal substrate comprises titanium.
7. A method for reducing metal-catalyzed reactions of sample components during liquid chromatography, the method comprising: Separate the sample in the chromatographic column of claim 1; as well as A detector is used to detect the separated sample components.
8. The method of claim 7, wherein the glass material comprises a pure or substantially pure titanium substrate, thereby forming a pure or substantially pure titanium glass material.
9. The method of claim 7, wherein the glass material comprises a titanium alloy substrate, thereby forming a titanium alloy glass material.
10. The method of claim 7, wherein the glass material comprises a stainless steel substrate, thereby forming a stainless steel glass material.
11. The method of claim 10, wherein the stainless steel glass stock comprises an intermediate coating applied prior to an outer coating, the outer coating comprising an inorganic-organic hybrid.
12. The method of claim 10, wherein the stainless steel glass stock comprises an intermediate layer applied simultaneously with an outer coating, the outer coating comprising an inorganic-organic hybrid.
13. The method of claim 7, wherein the external coating of the inorganic-organic hybrid comprises an alkylsilyl coating.
14. The method of claim 7, wherein the exposed metal wall within the chromatographic column is coated with an external coating comprising an inorganic-organic hybrid.
15. The method of claim 14, wherein the bio-inert pump is connected to the liquid chromatography system.
16. A method for improving chromatographic performance in the separation of samples containing amines, the method comprising: The sample is separated in an inert liquid chromatography system comprising a column, the column comprising a titanium glass material coated with an inorganic-organic hybrid coating, wherein the titanium glass material further comprises a vapor-deposited intermediate coating disposed between the inorganic-organic hybrid coating and the outer surface of the titanium glass material, wherein the intermediate coating is a metal-containing layer, wherein the metal-containing layer comprises titanium, a metal oxide, a metal nitride, or a metal carbide; and The separated components of the sample were detected using a UV detector or MS detector that is substantially free of oxidizing impurities.
17. The method of claim 16, wherein the inert liquid chromatography system further comprises a biological inert pump.
18. The method of claim 17, wherein the inert liquid chromatography system further comprises an internal column surface coated with an inorganic-organic hybrid coating.
19. The method of claim 16, wherein the titanium glass is coated with one or more layers of C2.
20. The method of claim 16, wherein the titanium glass is coated with a C2 base layer and a C2C10 top layer.
21. The method of claim 16, wherein the titanium glass frit is coated with a glycol-encapsulated inorganic-organic hybrid coating.
22. The method of claim 16, wherein the titanium glass frit is coated with a phenyl-encapsulated inorganic-organic hybrid coating.
23. An inert glass buffer for a liquid chromatography column, said inert glass buffer comprising: A stainless steel substrate comprising a multilayer coating, wherein the multilayer coating comprises a vapor-deposited titanium layer adjacent to the stainless steel substrate and an outer layer comprising an inorganic-organic hybrid coating.
24. An inert glass buffer for a liquid chromatography column, said inert glass buffer comprising: A substantially pure titanium substrate, wherein a C2 and / or C2C10 coating covers all outer surfaces to prevent analyte-metal interactions in the liquid chromatography column, wherein the substantially pure titanium substrate further comprises a vapor-deposited intermediate coating disposed between the C2 and / or C2C10 coating and the outer surface of the substantially pure titanium substrate, wherein the intermediate coating is a metal-containing layer, wherein the metal-containing layer comprises titanium, metal oxide, metal nitride, or metal carbide.
Citation Information
Patent Citations
Sinter Bonded Porous Metallic Coatings
US20120183799A1
Use of vapor deposition coated flow paths for improved chromatography of metal interacting analytes
US20190086371A1
Use of vapor deposition coated flow paths for improved analytical analysis
US20200215457A1